2010
DOI: 10.3892/ijmm_00000455
|View full text |Cite
|
Sign up to set email alerts
|

The anti-cancer efficacy of curcumin scrutinized through core signaling pathways in glioblastoma

Abstract: Abstract. Curcumin has been verified as an anti-cancer compound via multiple molecular targets. Its effective mechanisms include cell cycle arrest, inducing apoptosis, suppressing oncogenes, and enhancing tumor suppressor genes. The resistance of cells to chemotherapy, however, derives from the variable genetic aberration of cancer cells. Consequently, the core signaling pathways of glioblastoma have been explored to evaluate the efficacy of curcumin in proceeding through mutated genes in those pathways. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Debata et al reported that the sunitinib-curcumin combination was effective in restoring the tumor suppressor activity of the RB gene in renal cancer cells (Debata et al 2013). Furthermore, Su et al reported that curcumin significantly enhanced p53 or markedly inhibited the RB pathway by suppressing RB phosphorylation in the signaling pathways of glioblastoma (Su et al 2010). These studies demonstrated the anti-tumor activity of curcumin and prompted further investigation of curcumin in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Debata et al reported that the sunitinib-curcumin combination was effective in restoring the tumor suppressor activity of the RB gene in renal cancer cells (Debata et al 2013). Furthermore, Su et al reported that curcumin significantly enhanced p53 or markedly inhibited the RB pathway by suppressing RB phosphorylation in the signaling pathways of glioblastoma (Su et al 2010). These studies demonstrated the anti-tumor activity of curcumin and prompted further investigation of curcumin in HCC.…”
Section: Discussionmentioning
confidence: 99%
“… Debata et al (2013) reported that the sunitinib-curcumin combination was effective in restoring the tumor suppressor activity of the RB gene in renal cancer cells. Furthermore, Su, Wang & Chiu (2010) reported that curcumin significantly enhanced p53 or markedly inhibited the RB pathway by suppressing RB phosphorylation in the signaling pathways of glioblastoma ( Su, Wang & Chiu, 2010 ). These studies demonstrated the anti-tumor activity of curcumin and prompted further investigation of curcumin in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The results also add to the growing evidence that induction of ROS is a primary mechanism of Tan II-A biological activity. 3, 22 Given that the ROS induction we observed is directly related to the concentration of reducing equivalent DTT, we predict that the ability to generate ROS in cells may be similarly controlled by cellular redox environment, which may help to explain the pleiotropic effects of Tan II-A and other tanshinones. The cell-based assays reported here suggest that Tan II-A is cytotoxic to both telomerase-positive and telomerase-negative cells, but that telomerase-positive cell lines were more sensitive to Tan II-A than telomerase-negative cells.…”
mentioning
confidence: 88%